Spillovers Inside Conglomerates: Incentives and Capital - Duchin, Ran; Goldberg, Amir; Sosyura, Denis (Review of Financial Studies, 2017)
Using hand-collected data on divisional managers at conglomerates, we find that a change in industry pay in one division generates spillovers on managerial pay in other divisions of the same firm. These spillovers arise only within the boundaries of a conglomerate. The intra-firm spillovers increase when conglomerates have excess cash and when managers have more influence over its distribution, but decline in the presence of strong governance. These spillovers are associated with weaker performance and lower firm value. Our evidence is consistent with simultaneous cross-subsidization via managerial compensation and capital budgets and suggests that these practices arise in similar firms. Received March 19, 2015; editorial decision August 30, 2016 by Editor Francesca Cornelli.